PENGARUH PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN DI BANK RAKYAT INDONESIA SYARIAH KANTOR CABANG BANDUNG SUNIARAJA - Fauzi, Yasir Muharram; Dewi, Diana Nurfadila (STIBANKS Al Ma'soem Bandung, 2020)
This research was conducted to find out how much influence the Training and Motivation on Employee Productivity at Bank Syariah Syariah Bandung Branch Office Suniaraja. This study employs associative quantitative method, with a population of all bank employees and using saturated or census samples so that a questionnaire of 42 is needed to determine employee responses. Use the same pattern. In addition to data from questionnaires that were processed using the IBM SPSS Statistics 23 application, the authors also obtained data from experts' theories about training and motivation for employee productivity to strengthen analysis.Theresults showed that the trigger event was dominated by motivation rather than training. This can be seen from the test results between the two variables after the indicators are entered, the validity test, the validity test and other calculation results.As if combined between the two, this study revealed that the existence of training and providing motivation is very influential on employee productivity.